Gold complex compounds that inhibit drug-resistant Staphylococcus aureus by targeting thioredoxin reductase - Tharmalingam, Nagendran; Xu, Shi; Felix, Lewis Oscar; Roy, Biswajit; Xian, Ming; Mylonakis, Eleftherios; Fuchs, Beth Burgwyn (Frontiers in Antibiotics, 2023)
Introduction There is a significant need for new antimicrobial compounds that are effective against drug-resistant microbes. Thioredoxin reductase (TrxR) is critical in redox homeostasis and was identified as a potential drug target and confirmed through inhibition by compounds auranofin and Bay11-7085. Methods Additional TrxR inhibitors were designed and found to exhibit antimicrobial activity against Gram-positive (Enterococcus faecium and Staphylococcus aureus) and glutathione-deficient bacteria (Helicobacter pylori). Investigational compounds were tested for antimicrobial activity, anti-biofilm efficacy, target impact, and cytotoxicity. Results The first-generation molecules AU1 and AU5 inhibited TrxR activity and inhibited methicillin-resistant S. aureus strain MW2 with minimal inhibitory concentrations (MIC) of 0.125 and 0.5 μg/mL, respectively. In an S. aureus enzymatic assay, AU1 inhibited TrxR enzymatic activity in a dose-dependent manner causing a decrease in intracellular free thiols. In addition, biofilm studies demonstrated that AU1 and AU5 reduced biofilm formation at 1X MIC and disrupted mature biofilms at 4X MIC. Cytotoxicity profiles were created using human cell lines and primary cells with LD50 exceeding MICs by at least 12X. Discussion Thus, AU1 and AU5 were TrxR inhibitors that yielded low-concentration antimicrobial activity impacting S. aureus in planktonic and biofilm forms with limited toxic liability.